Quick-drying leveling mortar for sticking rock plates as well as preparation method and application of quick-drying leveling mortar
By adding a flat mortar to add a polyethylene polypropylene fiber of the pyradic polyethylene, using the rapid response of cymbal base and epoxy resin to solve the problem of long -term maintenance of rock plates and flattening. Effect of strength.
Patent Information
- Application Number
- CN202411470549.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-21
AI Technical Summary
In the prior art, the rock slab laying leveling requires at least one week of maintenance time, resulting in low construction efficiency and low mortar strength.
Use a fast -drying flat mortar with a paste, including quartz sand, epoxy resin, cement, diluent, acidic anhydrial curing agent, curing promoter, and pyrite polystyrene closer to polypropylene fiber. The rapid opening of oxygen resin and the curing cross -linking response significantly reduced the curing time of the mortar.
The mortar was achieved at the beginning of 1 hour, the strength of the ≧ 30MPa was achieved within 1 hour, and the strength of the ≧ 30MPa significantly improved the construction efficiency, solved the problem of low mortar strength, and quickly tied and pasted the rock plate directly.
Smart Images

Figure BDA0005094571790000031 
Figure BDA0005094571790000081 
Figure BDA0005094571790000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of leveling mortars, and in particular to a quick-drying leveling mortar for sticking rock slabs, and a preparation method and application thereof. Background Art
[0002] Wall leveling is an important prerequisite and condition for wall surface decoration. It is inconvenient to decorate when the wall is bumpy. Especially before laying tiles or panels, the wall needs to be leveled. The leveling mortar used in existing wall leveling requires 7-15 days to level the base surface and cure. After the curing is completed, paving can be carried out.
[0003] Epoxy resin mortar is mainly composed of epoxy resin, curing agent, quartz sand, cement and other hardeners. It has good bonding strength, water resistance and corrosion resistance, and is widely used in rock slab bonding, concrete repair, track bolt hole fixing, etc. However, traditional epoxy resin mortar has problems such as slow curing speed and low strength after curing.
[0004] Adding polymer fibers, glass fibers, inorganic nanomaterials and other reinforcing agents to epoxy resin mortar is an effective method to improve the comprehensive performance of epoxy mortar. Among them, polyacrylonitrile fiber has high mechanical strength, high tensile modulus, and good fracture resistance, and is widely used in building materials such as epoxy resin, cement mortar, and concrete. The invention patent with announcement number CN106517959B discloses a surface-modified fiber-toughened epoxy mortar, which uses polyacrylonitrile fibers or polyvinyl alcohol fibers with a surface modified polydopamine coating to modify the epoxy mortar, and the resulting mortar has better toughness, flexural strength and compressive strength. However, the patent does not increase the curing speed of the epoxy mortar or reduce its curing time. Summary of the invention
[0005] The technical problem solved by the present invention is to solve the problem of low construction efficiency in the prior art that the paving and leveling of rock slabs requires at least one week of curing time before laying the rock slabs, and to solve the problem of low mortar strength.
[0006] The technical solution of the present invention is: a quick-drying leveling mortar for sticking rock slabs, comprising 100 parts by weight of quartz sand, 25-40 parts by weight of epoxy resin, 30-55 parts by weight of cement, 2-4 parts by weight of diluent, 20-36 parts by weight of anhydride curing agent, 0.6-1.4 parts by weight of curing accelerator, and 0.3-2 parts by weight of mercaptomethyl polystyrene grafted polyacrylonitrile fiber.
[0007] The preparation method of mercaptomethyl polystyrene grafted polyacrylonitrile fiber is as follows:
[0008] Step (1), washing the polyacrylonitrile fiber with acetone, then adding it to chlorobenzene for swelling for 12-18 hours, adding the swollen polyacrylonitrile fiber to an acetone solution containing 4-thioacetyl styrene and dibenzoyl peroxide, irradiating the grafting reaction under an ultraviolet light source in a nitrogen atmosphere for 6-12 hours, filtering, washing with xylene, and drying to obtain thioacetyl styrene grafted polyacrylonitrile fiber.
[0009] Step (2), adding thioacetyl styrene grafted polyacrylonitrile fiber into sodium hydroxide solution, stirring for reaction, then adding dilute hydrochloric acid, filtering, washing with water, and drying to obtain mercaptomethyl polystyrene grafted polyacrylonitrile fiber.
[0010] Preferably, in step (1), the molar concentration of 4-thioacetyl styrene in the acetone solution is 0.5-2 mol / L, and the molar concentration of dibenzoyl peroxide is 0.008-0.035 mol / L.
[0011] Preferably, in step (2), the mass concentration of the sodium hydroxide solution is 80-120 g / L.
[0012] Preferably, in step (2), the reaction temperature is 40-50° C. and the reaction time is 3-6 h.
[0013] Preferably, in step (2), dilute hydrochloric acid is added to adjust the pH of the solution to 5-6.
[0014] Preferably, the preparation method of 4-thioacetyl styrene is: add 4-chloromethyl styrene and potassium thioacetate in a molar ratio of 1: (1.6-2.4) to N, N-dimethylformamide, heat to 50-65°C in a nitrogen atmosphere, react for 4-8h, add water, then extract with dichloromethane, dry the organic phase with anhydrous sodium sulfate, filter, rotary evaporate the filtrate, and recrystallize the product in dichloromethane to obtain 4-thioacetyl styrene. The reaction formula is:
[0015]
[0016] Preferably, the quartz sand is composed of fine quartz sand and coarse quartz sand in a mass ratio of (25-33):(67-75); the average particle size of the fine quartz sand is 100-200 mesh; the average particle size of the coarse quartz sand is 20-50 mesh. The cement is high alumina cement or sulphoalumina cement.
[0017] Preferably, the diluent is AGE alkyl glycidyl ether; and the curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol DMP-30.
[0018] Preferably, the anhydride curing agent is methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride.
[0019] Preferably, the preparation method of quick-drying leveling mortar for sticking rock slabs is: add epoxy resin and mercaptomethyl polystyrene grafted polyacrylonitrile fiber to the diluent, add quartz sand, cement, and water after stirring, vibrate and degas after stirring, and finally add anhydride curing agent and curing accelerator, mix well, and obtain quick-drying leveling mortar for sticking rock slabs.
[0020] The technical effect of the invention is: using 4-thioacetyl styrene to carry out ultraviolet light irradiation grafting reaction on polyacrylonitrile fiber, and then hydrolyzing the thioacetyl group with sodium hydroxide to generate mercapto groups, thereby obtaining mercaptomethyl polystyrene grafted polyacrylonitrile fiber, thereby introducing polystyrene molecular chains containing mercapto groups on the surface of the polyacrylonitrile fiber.
[0021] The present invention uses quartz sand and epoxy resin as the main materials of epoxy mortar, anhydride curing agent, DMP-30 accelerator as the curing system, and mercaptomethyl polystyrene grafted polyacrylonitrile fiber as a filling and reinforcing agent to obtain a quick-drying leveling epoxy mortar. The surface of mercaptomethyl polystyrene grafted polyacrylonitrile fiber contains a large number of mercapto groups, and the added DMP-30 can not only be used as a curing accelerator for the anhydride curing agent, but also as a catalytic accelerator, which contains multiple tertiary amine groups, so that the mercapto group deprotonates hydrogen to generate active mercapto anions, which react rapidly with the epoxy resin to form a curing and cross-linking reaction, thereby accelerating the curing reaction of the epoxy resin and significantly reducing the curing time of the epoxy mortar.
[0022] The thiomethyl polystyrene grafted polyacrylonitrile fiber of the present invention undergoes a curing crosslinking reaction with the epoxy resin, and the polyacrylonitrile fiber is grafted into the epoxy resin molecular chain through chemical bonding, thereby enhancing the compatibility and bonding strength of the polyacrylonitrile fiber and the epoxy resin, improving the dispersibility of the polyacrylonitrile fiber in the epoxy mortar, and the polystyrene molecular chain grafted with polyacrylonitrile has the advantages of high strength and high structural stability, thereby significantly improving the compressive strength and flexural strength of the epoxy mortar. The obtained epoxy mortar has good practical applications in wall leveling materials, rock slab pasting materials, road repair materials, floor materials, etc. In actual application, this product has initial setting within 1 hour and final setting within 3 hours, reaching a strength of ≧30MPa, and the base surface leveling can be completed within 3 hours, and the rock slab can be directly pasted after leveling, achieving rapid leveling, no need for maintenance, short-time curing, and direct tile pasting. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] (1) Add 50 mmol 4-chloromethylstyrene and 120 mmol potassium thioacetate to 1000 mL N,N-dimethylformamide, heat to 55°C in a nitrogen atmosphere, react for 8 hours, add water, and then extract with dichloromethane. The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is rotary evaporated. The product is recrystallized from dichloromethane to obtain 4-thioacetylstyrene.
[0026] (2) The polyacrylonitrile fiber was washed with acetone and then added to chlorobenzene for swelling for 18 hours. 10 g of the swollen polyacrylonitrile fiber was added to 400 mL of an acetone solution containing 4-thioacetyl styrene and dibenzoyl peroxide, and the molar concentration of 4-thioacetyl styrene in the acetone solution was controlled to be 1.2 mol / L and the molar concentration of dibenzoyl peroxide was controlled to be 0.023 mol / L. In a nitrogen atmosphere, a high-pressure mercury lamp was used as an ultraviolet light source to irradiate and carry out a grafting reaction for 8 hours. The fiber was filtered, washed with xylene, and dried to obtain thioacetyl styrene grafted polyacrylonitrile fiber.
[0027] (3) Add thioacetyl styrene grafted polyacrylonitrile fiber to a sodium hydroxide solution with a mass concentration of 120 g / L, heat to 40°C, stir and react for 4 hours, then add dilute hydrochloric acid to pH 6, filter, wash with water, and dry to obtain thiomethyl polystyrene grafted polyacrylonitrile fiber.
[0028] (4) Add 340g of epoxy resin 51 and 3g of mercaptomethyl polystyrene grafted polyacrylonitrile fiber to 32g of diluent AGE alkyl glycidyl ether, stir, add 280g of quartz sand fine material with an average particle size of 200 mesh, 720g of quartz sand coarse material with an average particle size of 20 mesh, 420g of high alumina cement, 220mL of water, stir and vibrate to degas, finally add 300g of acid anhydride curing agent methyl hexahydrophthalic anhydride and 11g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30, mix well, and obtain quick-drying leveling mortar for bonding rock slabs.
[0029] Example 2
[0030] (1) Add 50 mmol 4-chloromethylstyrene and 100 mmol potassium thioacetate to 800 mL N,N-dimethylformamide, heat to 50°C in a nitrogen atmosphere, react for 8 hours, add water, and then extract with dichloromethane. The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is rotary evaporated. The product is recrystallized from dichloromethane to obtain 4-thioacetylstyrene.
[0031] (2) The polyacrylonitrile fiber was washed with acetone and then added to chlorobenzene for swelling for 18 hours. 10 g of the swollen polyacrylonitrile fiber was added to 400 mL of an acetone solution containing 4-thioacetyl styrene and dibenzoyl peroxide, and the molar concentration of 4-thioacetyl styrene in the acetone solution was controlled to be 2 mol / L, and the molar concentration of dibenzoyl peroxide was controlled to be 0.035 mol / L. In a nitrogen atmosphere, a high-pressure mercury lamp was used as an ultraviolet light source to irradiate and carry out a grafting reaction for 12 hours. The fiber was filtered, washed with xylene, and dried to obtain thioacetyl styrene grafted polyacrylonitrile fiber.
[0032] (3) Add thioacetyl styrene grafted polyacrylonitrile fiber to a sodium hydroxide solution with a mass concentration of 120 g / L, heat to 40°C, stir and react for 6 hours, then add dilute hydrochloric acid to pH 6, filter, wash with water, and dry to obtain thiomethyl polystyrene grafted polyacrylonitrile fiber.
[0033] (4) Add 250g of epoxy resin 51 and 3g of mercaptomethyl polystyrene grafted polyacrylonitrile fiber to 20g of diluent AGE alkyl glycidyl ether, stir, add 330g of quartz sand fine material with an average particle size of 100 mesh, 670g of quartz sand coarse material with an average particle size of 20 mesh, 550g of high alumina cement, 300mL of water, stir and vibrate to degas, finally add 200g of acid anhydride curing agent methyltetrahydrophthalic anhydride and 6g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30, mix well, and obtain quick-drying leveling mortar for bonding rock slabs.
[0034] Example 3
[0035] (1) Add 50 mmol 4-chloromethylstyrene and 80 mmol potassium thioacetate to 800 mL N,N-dimethylformamide, heat to 65°C in a nitrogen atmosphere, react for 4 hours, add water, and then extract with dichloromethane. The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is rotary evaporated. The product is recrystallized in dichloromethane to obtain 4-thioacetylstyrene.
[0036] (2) The polyacrylonitrile fiber was washed with acetone and then added to chlorobenzene for swelling for 12 hours. 10 g of the swollen polyacrylonitrile fiber was added to 400 mL of an acetone solution containing 4-thioacetyl styrene and dibenzoyl peroxide, and the molar concentration of 4-thioacetyl styrene in the acetone solution was controlled to be 0.5 mol / L and the molar concentration of dibenzoyl peroxide was controlled to be 0.008 mol / L. In a nitrogen atmosphere, a high-pressure mercury lamp was used as an ultraviolet light source to irradiate and carry out a grafting reaction for 6 hours. The fiber was filtered, washed with xylene, and dried to obtain thioacetyl styrene grafted polyacrylonitrile fiber.
[0037] (3) Add thioacetyl styrene grafted polyacrylonitrile fiber to a sodium hydroxide solution with a mass concentration of 80 g / L, heat to 50°C, stir and react for 3 hours, then add dilute hydrochloric acid to pH 5, filter, wash with water, and dry to obtain thiomethyl polystyrene grafted polyacrylonitrile fiber.
[0038] (4) Add 400g of epoxy resin 51 and 3g of mercaptomethyl polystyrene grafted polyacrylonitrile fiber to 40g of diluent AGE alkyl glycidyl ether, stir, add 250g of quartz sand fine material with an average particle size of 100 mesh, 750g of quartz sand coarse material with an average particle size of 50 mesh, 300g of sulphoaluminum cement, 130mL of water, stir and vibrate to degas, finally add 360g of acid anhydride curing agent methyl hexahydrophthalic anhydride and 14g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30, mix well, and obtain quick-drying leveling mortar for bonding rock slabs.
[0039] Example 4
[0040] (1) According to the method of Example 1, mercaptomethyl polystyrene grafted polyacrylonitrile fibers were prepared.
[0041] (2) Add 340g of epoxy resin 51 and 12g of mercaptomethyl polystyrene grafted polyacrylonitrile fiber to 32g of diluent AGE alkyl glycidyl ether, stir, add 280g of quartz sand fine material with an average particle size of 200 mesh, 720g of quartz sand coarse material with an average particle size of 20 mesh, 420g of high alumina cement, 220mL of water, stir and vibrate to degas, finally add 300g of acid anhydride curing agent methyl hexahydrophthalic anhydride and 11g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30 to obtain quick-drying leveling mortar for bonding rock slabs.
[0042] Example 5
[0043] (1) According to the method of Example 1, mercaptomethyl polystyrene grafted polyacrylonitrile fibers were prepared.
[0044] (2) Add 340g of epoxy resin 51 and 20g of mercaptomethyl polystyrene grafted polyacrylonitrile fiber to 32g of diluent AGE alkyl glycidyl ether, stir, add 280g of quartz sand fine material with an average particle size of 200 mesh, 720g of quartz sand coarse material with an average particle size of 20 mesh, 420g of high alumina cement, 220mL of water, stir and vibrate to degas, finally add 300g of acid anhydride curing agent methyl hexahydrophthalic anhydride and 11g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30, mix well, and obtain quick-drying leveling mortar for bonding rock slabs.
[0045] Comparative Example 1
[0046] (1) Add 340 g of epoxy resin 51 to 32 g of AGE alkyl glycidyl ether as a diluent, stir, add 280 g of quartz sand fine material with an average particle size of 200 mesh, 720 g of quartz sand coarse material with an average particle size of 20 mesh, 420 g of high alumina cement, and 220 mL of water, stir, vibrate and degas, and finally add 300 g of anhydride curing agent methyl hexahydrophthalic anhydride and 11 g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30, mix well, and obtain a quick-drying leveling mortar for bonding rock slabs.
[0047] Comparative Example 2
[0048] (1) Add 340g of epoxy resin 51 and 3g of polyacrylonitrile fiber to 32g of diluent AGE alkyl glycidyl ether, stir and add 280g of quartz sand fine material with an average particle size of 200 mesh, 720g of quartz sand coarse material with an average particle size of 20 mesh, 420g of high alumina cement, and 220mL of water. Stir and vibrate to degas. Finally, add 300g of acid anhydride curing agent methyl hexahydrophthalic anhydride and 11g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30, mix well, and obtain quick-drying leveling mortar for bonding rock slabs.
[0049] Comparative Example 3
[0050] (1) Thioacetyl styrene grafted polyacrylonitrile fiber was prepared according to the method of Example 1.
[0051] (2) Add 340g of epoxy resin 51 and 3g of thioacetylstyrene grafted polyacrylonitrile fiber to 32g of diluent AGE alkyl glycidyl ether, stir and add 280g of quartz sand fine material with an average particle size of 200 mesh, 720g of quartz sand coarse material with an average particle size of 20 mesh, 420g of high alumina cement, and 220mL of water. Stir and vibrate to degas. Finally, add 300g of acid anhydride curing agent methyl hexahydrophthalic anhydride and 11g of curing accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP-30, mix well, and obtain quick-drying leveling mortar for bonding rock slabs.
[0052] The high alumina cement used in the above examples and comparative examples is CA-50 high alumina cement, produced by Zhengzhou Zhongtai Cement Co., Ltd.
[0053] Pour the quick-drying leveling mortar for sticking the rock slab into the mold and cure it at 90°C; determine the curing time of the epoxy mortar according to the GB / T1346-2011 method.
[0054] The cured epoxy mortar specimens were placed at room temperature for 7-28 days with a humidity of 80% RH; the compressive strength and flexural strength of the specimens were measured according to the GBT17671-2021 method. The test results are shown in Tables 1-3.
[0055] Table 1 Epoxy mortar curing performance test
[0056]
[0057]
[0058] It can be seen from the above table that the curing time of the epoxy mortar in Examples 1-5 is only 25-55 min, and the curing speed is fast. This is mainly because the surface of the added mercaptomethyl polystyrene grafted polyacrylonitrile fiber contains a large number of mercapto groups, and the added DMP-30 can be used as a catalyst promoter, which contains multiple tertiary amine groups, so that the mercapto group deprotonates hydrogen to generate active mercapto anions, which react rapidly with the epoxy resin to undergo a ring-opening reaction, thereby causing the mercaptomethyl polystyrene grafted polyacrylonitrile fiber to undergo a curing and cross-linking reaction with the epoxy resin, thereby accelerating the curing reaction of the epoxy resin and significantly reducing the curing time of the epoxy mortar.
[0059] Comparative Example 1 does not add mercaptomethyl polystyrene grafted polyacrylonitrile fiber, and the polyacrylonitrile fibers added in Comparative Examples 2 and 3 do not contain mercapto groups, and cannot undergo a rapid curing reaction with the epoxy resin, and do not reduce the curing time of the epoxy mortar.
[0060] Table 2 Compressive strength test of epoxy mortar
[0061]
[0062] Table 3 Flexural strength test of epoxy mortar
[0063]
[0064]
[0065] It can be seen from Table 1 and Table 2 that, compared with Example 1, the epoxy mortar in Examples 1-5 is added with mercaptomethyl polystyrene grafted polyacrylonitrile fiber, and under the catalytic promotion of DMP-30, the mercapto group reacts with the epoxy resin, so that the mercaptomethyl polystyrene grafted polyacrylonitrile fiber and the epoxy resin undergo a curing and cross-linking reaction, and the polyacrylonitrile fiber is grafted into the epoxy resin molecular chain through chemical bonding, thereby enhancing the compatibility and bonding strength of the polyacrylonitrile fiber and the epoxy resin, improving the dispersibility of the polyacrylonitrile fiber in the epoxy mortar, and the polystyrene molecular chain grafted with polyacrylonitrile has the advantages of high strength and high structural stability, thereby significantly improving the compressive strength and flexural strength of the epoxy mortar.
[0066] Compared with Example 1, the polyacrylonitrile fibers added in Comparative Examples 2 and 3 do not contain mercapto groups and cannot undergo a rapid curing reaction with the epoxy resin, resulting in low compatibility and bonding strength between the polyacrylonitrile fibers and the epoxy resin, poor reinforcement effect on the epoxy mortar, and significantly lower compressive strength and flexural strength than Example 1.
[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A quick-drying leveling mortar for sticking rock slabs, characterized in that: The quick-drying leveling mortar for sticking rock slabs comprises 100 parts by weight of quartz sand, 25-40 parts by weight of epoxy resin, 30-55 parts by weight of cement, 2-4 parts by weight of diluent, 20-36 parts by weight of anhydride curing agent, 0.6-1.4 parts by weight of curing accelerator, and 0.3-2 parts by weight of mercaptomethyl polystyrene grafted polyacrylonitrile fiber; The preparation method of the mercaptomethyl polystyrene grafted polyacrylonitrile fiber is: Step (1), washing the polyacrylonitrile fiber with acetone, then adding it to chlorobenzene for swelling for 12-18 hours, adding the swollen polyacrylonitrile fiber to an acetone solution containing 4-thioacetyl styrene and dibenzoyl peroxide, irradiating the grafting reaction under an ultraviolet light source in a nitrogen atmosphere for 6-12 hours, filtering, washing, and drying to obtain thioacetyl styrene grafted polyacrylonitrile fiber; Step (2), adding thioacetyl styrene grafted polyacrylonitrile fiber into sodium hydroxide solution, stirring for reaction, then adding dilute hydrochloric acid, filtering, washing, and drying to obtain mercaptomethyl polystyrene grafted polyacrylonitrile fiber.
2. The quick-drying leveling mortar for sticking rock slabs according to claim 1 is characterized in that: In the step (1), the molar concentration of 4-thioacetyl styrene in the acetone solution is 0.5-2 mol / L, and the molar concentration of dibenzoyl peroxide is 0.008-0.035 mol / L.
3. The quick-drying leveling mortar for sticking rock slabs according to claim 1 is characterized in that: In the step (2), the mass concentration of the sodium hydroxide solution is 80-120 g / L.
4. The quick-drying leveling mortar for sticking rock slabs according to claim 1 is characterized in that: In the step (2), the reaction temperature is 40-50°C and the reaction time is 3-6h.
5. The quick-drying leveling mortar for sticking rock slabs according to claim 1 is characterized in that: In the step (2), dilute hydrochloric acid is added to adjust the pH of the solution to 5-6.
6. The quick-drying leveling mortar for sticking rock slabs according to claim 2, characterized in that: The preparation method of 4-thioacetyl styrene comprises: adding 4-chloromethyl styrene and potassium thioacetate in a molar ratio of 1:(1.6-2.4) to N,N-dimethylformamide, heating to 50-65° C. in a nitrogen atmosphere, reacting for 4-8 hours, adding water, then extracting with dichloromethane, and recrystallizing to obtain 4-thioacetyl styrene.
7. The quick-drying leveling mortar for sticking rock slabs according to claim 1 is characterized in that: The quartz sand is composed of fine quartz sand and coarse quartz sand in a mass ratio of (25-33):(67-75); the average particle size of the fine quartz sand is 100-200 meshes; the average particle size of the coarse quartz sand is 20-50 meshes; and the cement is high-alumina cement or sulphoalumina cement.
8. The quick-drying leveling mortar for sticking rock slabs according to claim 1, characterized in that: The diluent is AGE alkyl glycidyl ether; and the curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
9. The quick-drying leveling mortar for sticking rock slabs according to claim 1, characterized in that: The acid anhydride curing agent is methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride.
10. A method for preparing the quick-drying leveling mortar for bonding rock slabs according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: adding epoxy resin and mercaptomethyl polystyrene grafted polyacrylonitrile fiber into a diluent, adding quartz sand, cement and water after stirring, vibrating and degassing after stirring, and finally adding anhydride curing agent and curing accelerator, mixing well to obtain a quick-drying leveling mortar for sticking rock slabs.
Citation Information
Patent Citations
A surface-modified fiber-toughened epoxy mortar
CN106517959B
Preparation method and application of ultra-high molecular weight polyethylene fiber
CN116427171A
Method for production of carbon black graft polymer
EP0749991A2
Palladium solid phase extraction material and manufacturing method therefor
JP2017205745A
Manufacturing process of fiber-cement composite materials using portland cement reinforced with inorganic fibers chemically modified by organoselanes
WO2009135279A2
Cited By
Anti-layering light super-soft rock plate binder and preparation method thereof
CN120903900A